Trends and Limitations in the Assessment of the Contractile Properties of Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes From Patients With Dilated Cardiomyopathy - Ito, Masamichi; Nomura, Seitaro; Morita, Hiroyuki; Komuro, Issei (Frontiers in Cardiovascular Medicine, 2020)
The application of human induced pluripotent stem cell-derived cardiomyocytes (hiPSCMs) from patients is expected in disease modeling and drug screening in vitro. Dilated cardiomyopathy (DCM) is an intractable disease characterized by the impairment of systolic function and leads to severe heart failure. A number of researchers have focused on disease modeling of DCM and reproduced its pathologic phenotypes in hiPSCMs, but a robust method to evaluate the contractile properties of cardiomyocytes in vitro has not been standardized. In addition, it is unknown whether the throughput of measurements and analyses could be increased sufficiently for compound screening. Here, we reviewed the articles in which the contractile abnormalities of DCM hiPSCMs were recapitulated and assessed the trends and problems in sample preparation and evaluation. We found that single-cell level analysis was ineffective in some cases, and a tissue engineering approach has become dominant recently because of its increased efficiency in reproducing impaired contractility. We also examined two commercially available automated measurement devices with moderate throughput for motion analysis using two-dimensional hiPSCM sheets composed of originally established DCM hiPSCMs. As a result, both of the tested devices, an impedance analyzer and a video image-based cell motion analyzer, were not effective in detecting the expected reduction of contractility in the DCM clone. These findings collectively suggest that a tissue engineering approach could expand the potential of disease modeling with hiPSCMs, and so far, appropriate methods for in vitro force measurement with sufficient throughput, but without sacrificing physiological fidelity, are awaited.